Employment With Asymmetric Information - Azariadis, Costas (Quarterly Journal of Economics, 1983)
In an economy without informational and other distortions, entrepreneurs and workers can write labor contracts that support a Pareto optimal allocation of resources. This paper is an attempt to characterize contracts when enterpreneurs are better informed about the state of nature than are their workers. Asymmetric information generally results in a suboptimal allocation of both risk and worker effort; in particular, if consumption and leisure are perfect substitutes, employment will be less than fully Pareto optimal in all but the most favorable states of nature.